P29 Proximal lower limb strength and balance in chronic ankle instability. (17th September 2017) - Khalaj, N; Vicenzino, B; Smith, MD
Abstract : Study Design: Case-control. Objectives: To compare proximal lower limb muscle strength in chronic ankle instability (CAI), healthy controls and copers (individuals with one previous ankle and no ongoing problems), and investigate the relationship between proximal lower limb strength and balance. Background: CAI is associated with altered lower kinetic chain biomechanics and balance. Proximal lower limb strength is essential for control of distal segments and may contribute to kinematic observations and balance deficits in this population. Methods and Measures: Isometric strength of the hip and knee was measured using a securely fixated hand-held dynamometer in 22 CAI participants, 22 controls and 14 copers, matched for aged, sex, physical activity level, and leg dominance. The Star Excursion Balance Test was used to assess anterior, posterior-lateral (PL), and posterior-medial (PM) balance. Standardised Mean Differences (SMD) and Pearson's Correlation Coefficient are reported herein as point estimates of effect. Results: There were large SMD (>1.2) for strength deficits of all hip and knee muscles in CAI participants compared to controls, with the exception of the hip internal and external rotators. Flexors and extensors of the hip and knee exhibited moderate deficits (SMD 1) in participants with CAI compared to copers. Balance was impaired in CAI participants compared to healthy controls and copers in all movement directions. There was a strong positive correlation between abductor strength and PL balance (R=0.526), and moderate positive correlations between knee strength (R=0.434) and hip extensor strength (R=0.454) and PL balance. Conclusion: Decreased proximal lower limb strength is present in CAI and is associated with impaired balance. Proximal lower limb strengthening could be considered when addressing balance deficits in this population.